2000
DOI: 10.1016/s0022-5347(05)67538-6
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Post-Radical Prostatectomy Incontinence: A Clinical and Video Urodynamic Study

Abstract: Sphincteric incontinence is the most common urodynamic finding in patients with post-radical prostatectomy incontinence, although other findings may coexist. The most accurate diagnosis is attained when all objective measures are put in perspective with the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
1
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(140 citation statements)
references
References 21 publications
0
133
1
6
Order By: Relevance
“…Urodynamic studies of UI in patients following radical prostatectomy demonstrated sphincteric deficiency as the major or sole cause in approximately two thirds of patients. 43 Isolated bladder overactivity occurred in only 6%, but overactivity was associated with sphincter deficiency in one third of patients. An obstructed voiding pattern may be due to an outlet stricture (clinically relevant in only 6% of patients, usually located at the vesico-urethral anastomosis and occasionally in the more distal urethra) or to impaired detrusor contractility resulting from operative neurological injury and fibrosis.…”
Section: Assessment Of Urinary Incontinencementioning
confidence: 99%
“…Urodynamic studies of UI in patients following radical prostatectomy demonstrated sphincteric deficiency as the major or sole cause in approximately two thirds of patients. 43 Isolated bladder overactivity occurred in only 6%, but overactivity was associated with sphincter deficiency in one third of patients. An obstructed voiding pattern may be due to an outlet stricture (clinically relevant in only 6% of patients, usually located at the vesico-urethral anastomosis and occasionally in the more distal urethra) or to impaired detrusor contractility resulting from operative neurological injury and fibrosis.…”
Section: Assessment Of Urinary Incontinencementioning
confidence: 99%
“…Nonetheless, 95% of men with postprostatectomy urinary leakage to any degree tend to describe symptoms consistent with stress urinary incontinence (SUI) that are documented on urodynamic studies. [16,17] …”
Section: Etiologymentioning
confidence: 99%
“…Broadly, these include detrusor over-and underactivity, decreased vesical compliance, ISD, and bladder outlet obstruction, as in the case of anastomotic strictures. [16,50] The presence of these factors pre-operatively must also be considered. Most cases of incontinence are a result of intraoperative damage to the native urinary sphincteric mechanisms [11] , particularly the intrinsic sphincter component.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative incontinence is a common side effect after prostatectomy that can severely impact quality of life [2 -6]. The pathophysiology of incontinence is largely due to extrinsic sphincter insufficiency; however may be exacerbated by various other factors [7].…”
Section: Introductionmentioning
confidence: 99%